A utilização de uma abordagem comunicativa no ensino de inglês em turmas de adolescentes do ensino médio. - Lima, Rosangela Nunes de (2007)
English is used by enormous number of people in the world, and most learners of English can be found in monolingual classes in Brazil, where all the students share a common language Portuguese. It has been a practical concern throughout history the reflection on finding more efficient and more effective ways of teaching languages. Many theoreticians in the field of Applied Linguistics have worked on research to provide a background for discussion of new ideas which are based on different theories of how people learn a foreign language. The objective of this work is to look for answers and instruments, in the specific field of English language teaching, in a classroom of adolescents, through the introduction of teaching materials used with a communicative approach, which will emphasize the processes of communication in a way that will help the students realize that the learning of a foreign language can be used as a real means of communication. The data were collected by recording in audio, as well as by taking field notes. This study suggests that there was a natural interest by the students in trying to communicate in English, without fear of corrections, and sometimes in starting conversations in this foreign language. Finally, the aim of this study is to offer teachers of English suggestions, as well as provide directions for further research in classrooms, to what concerns the process of teaching and learning a foreign language, in a way that we, English teachers, can teach our students, not to speak about the English language, but speak the English language.